PROGNOSTIC SIGNIFICANCE OF SERUM ALBUMIN IN DIFFUSE LARGE B-CELL LYMPHOMA IN THE PRERITUXIMAB AND RITUXIMAB ERA - Tadić, Ljiljana Lj; Krstić, Nikola (Acta medicae Medianae, 2022)
Diffuse large B cell lymphoma (DLBCL) is the most frequent subgroup of non-Hodgkin lymphoma. The aim of the author was to verify the existence of important pretreatment serum albumin (SA) level as an independent factor of disease prognosis in patients with DLBCL in the territory of Southeast Serbia, in the era of prerituximab and rituximab.A total of 55 patients with DLBCL (R-CHOP group) and 14 patients (CHOP group) were included in the study. Patients were divided into 2 groups according to the value of pretreatment SA: SA 30 g/l and ≤ 30 g/l. We analyzed the correlation of SA value with clinical stage and age, as well as the survival of patients with DLBCL compared to SA according to a therapeutic protocol.There was no significant correlation of SA with age (p = 0.630), clinical stage (p = 0.943) and survival (p = 0.638) in CHOP group. There was significant correlation between SA levels with survival (p = 0.001) in R-CHOP group. No significant correlation of SA with age (p = 0.141) and clinical stage of disease (p = 0.305). There was no significant difference in survival compared to the value of SA in CHOP group/Log-rank = 0.782. There was significant difference in survival compared to the value of SA in R-CHOP group/Log-rank = 0.002.The relationship between the predictive value of SA and the treatment protocol for DLBCL evaluated by the logistic regression analysis showed that the level of SA was not a significant predictor for the choice of treatment (Wald = 1.540, p > 0.05)Our research has confirmed a negative predictive value of pretreatment serum albumin levels in patients with DLBCL treated according to R-CHOP protocol. Retrospective studies with a larger number of DLBCL patients who were treated with CHOP protocol, would give more significant results for the predictive importance of SA. Prognostic indexes, which as part of the point system include the value of SA, can be very useful in predicting patients with DLBCL.
Keywords: DLBCL, albumin, R-CHOP, CHOP